Online pre-loved / second-hand book system - Lee, Hui Nee (2024)
project is to build an online preloved book system for helping the people to sell the preloved books to the one who needs. The Online Preloved Book System is an e-commerce platform that helps users to sell and buy second-hand books. There are six problems has been found in most of the existing system which are lack of Online Pre-loved system that only sells book category in mobile application, lack of interactivity between buyer and seller, lack of Wishlist, lack of book recommender, lack of favourite list and lack of seller feature. Therefore, this online preloved book system will be doing as a mobile application where nowadays most people have their own mobile phone so it will be convenient if user can use the system as a mobile application. The system has involved one user as a person which is a person can be a book seller and book buyer or only seller or only buyer. Method that has been applied to develop an online pre-loved book system is SDLC, and the software are Android Studio, Java programming language and Firebase. In conclusion, the Online Preloved Book System is a convenient and user-friendly platform for buying and selling used books online. Besides, it also help the user to find their favourite book by providing a chatbot that is doing book recommender. It provides a great opportunity for book lovers to share their passion for books and help to reduce waste by giving preloved books a new home.